Risk Factors for the Development of Post-Traumatic Hydrocephalus in Children - Elsamadicy, Aladine A. (World Neurosurg, 2020)
OBJECTIVE: The aim of this study was to investigate the national impact of demographic, hospital, and inpatient risk factors on posttraumatic hydrocephalus (PTH) development in pediatric patients who presented to the emergency department after a traumatic brain injury (TBI). METHODS: The Nationwide Emergency Department Sample database 2010–2014 was queried. Patients (<21 years old) with a primary diagnosis of TBI and subsequent secondary diagnosis of PTH were identified using the International Classification of Diseases, Ninth Revision, Clinical Modification coding system. RESULTS: We identified 1,244,087 patients who sustained TBI, of whom 930 (0.07%) developed PTH. The rates of subdural hemorrhage and subarachnoid hemorrhage were both significantly higher for the PTH cohort. On multivariate regression, age 6–10 years (odds ratio [OR], 0.6; 95% confidence interval [CI], 0.38–0.93; P = 0.022), 11–15 years (OR, 0.32; 95% CI, 0.21–0.48; P < 0.0001), and 16–20 years (OR, 0.24; 95% CI, 0.15–0.37; P < 0.0001) were independently associated with decreased risk of developing hydrocephalus, compared with ages 0–5 years. Extended loss of consciousness with baseline return and extended loss of consciousness without baseline return were independently associated with increased risk of developing hydrocephalus. Respiratory complication (OR, 28.35; 95% CI, 15.75–51.05; P < 0.0001), hemorrhage (OR, 37.12; 95% CI, 4.79–287.58; P = 0.0001), thromboembolic (OR, 8.57; 95% CI, 1.31–56.19; P = 0.025), and neurologic complication (OR, 64.64; 95% CI, 1.39–3010.2; P = 0.033) were all independently associated with increased risk of developing hydrocephalus. CONCLUSIONS: Our study using the Nationwide Emergency Department Sample database shows that various demographic, hospital, and clinical risk factors are associated with the development of hydrocephalus after traumatic brain injury.